2012
DOI: 10.1021/jp307031b
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Enlightening of the Local Structure Of VOX Active Sites in Catalysts for the Odh of Propane

Abstract: Site isolation of V active sites has been often correlated to catalytic performance for the oxidative dehydrogenation (ODH) of propane to propylene. In particular, catalyst selectivity seems favoured by high V dispersion. The latter property is hardly attainable by traditional preparation methods, especially by impregnation except at very low V loading, which however may lead to a too high surface exposure of the acidic sites of the support. In this paper, the effect of the preparation procedure on catalyst pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 59 publications
0
24
0
1
Order By: Relevance
“…The molecular structures of surface vanadia species on metal oxide supports have been reported in the technical literature [85][86][87][88]. These studies suggest that, depending on the vanadium loading on the support, four kinds of VO x surface species can be present on the catalyst surface: (a) isolated VO 4 species (monovanadate); (b) polymeric VO 4 species (polyvanadates); (c) a mix of both isolated and polymeric VO 4 surface species; and, (d) V 2 O 5 crystals.…”
Section: Vo X Surface Coveragementioning
confidence: 99%
“…The molecular structures of surface vanadia species on metal oxide supports have been reported in the technical literature [85][86][87][88]. These studies suggest that, depending on the vanadium loading on the support, four kinds of VO x surface species can be present on the catalyst surface: (a) isolated VO 4 species (monovanadate); (b) polymeric VO 4 species (polyvanadates); (c) a mix of both isolated and polymeric VO 4 surface species; and, (d) V 2 O 5 crystals.…”
Section: Vo X Surface Coveragementioning
confidence: 99%
“…45 This indicates that the activity and selectivity of the V-based catalysts for ODP does not depend solely on their reducibility 6,43 but is influenced by other factors, for instance, the interaction with the support, 20,43 dispersion of the active phase, 29,46,47 V-O binding energy, 45 and acid-base properties. 48 Considering that α-NaVO 3 /1 and β-NaVO 3 /1 contain similar species, but show distinct catalytic activity (vide infra), we were interested to compare H 2 -TPR profiles of these two catalysts. A slightly lower T max was observed for the more active catalyst, β-NaVO 3 /1, as compared to α-NaVO 3 /1 (555 and 580°C, respectively, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…An important parameter is the amount of vanadium oxide on the support, which determines the nature of the active species, their dispersion and consequently influences the reaction mechanism [17,18,19,20,21,22,23,24,25]. It was demonstrated that the selectivity to propene was higher in the presence of isolated VO x species.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the selectivity to propene was higher in the presence of isolated VO x species. By increasing the vanadium loading, the isolated VO x species tend to oligomerize, with the formation of V 2 O 5 species: the higher the vanadium load, the greater the conversion, but the lower the propene selectivity, as vanadia favours the complete combustion to CO and CO 2 [21,22,24,25,26,27].…”
Section: Introductionmentioning
confidence: 99%